HIRUK PIKUK PERAN DAN FUNGSI DEWAN PENGUPAHAN: Suatu Kajian Terhadap perjalanan Penetapan Upah Minimum Kabupaten (UMK) Kabupaten Mojokerto - santosa, santosa; Wijaya, Dian (Universitas Islam Majapahit, Indonesia, 2024)
This paper will conduct a criminological study of the determination of the UMK based on the KHL, productivity and taking into account economic growth, which raises problems. First, there is a